Soldering paste free of soldering flux residue and splashing and preparation method of soldering paste
By adding epoxy resin, thermoplastic resin and other components to the solder paste, adjusting the ratio and adding solvents, the problem of flux splashing during the welding process is solved, and the welding efficiency and product quality are improved.
Patent Information
- Application Number
- CN202311234058.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-23
- Publication Date
- 2025-03-25
AI Technical Summary
When welding large base station antenna filters, fluxes in ordinary solder paste are prone to spilling and splashing, causing internal contamination of the filter, affecting the resonant parameters, and requiring a lot of manual adjustments.
A solder paste containing epoxy resin, thermoplastic resin, solder paste and solder alloy powder is used to reduce the viscosity of the solder paste and reduce the splash of flux by adjusting the ratio and adding solvents, diluents, active agents and corrosion inhibitors.
It effectively reduces the spillover and splashing of flux, reduces pollution during welding, improves welding efficiency, and reduces the need for resonant parameter adjustment.
Smart Images

Figure BDA0004465065660000051 
Figure BDA0004465065660000061 
Figure HDA0004465065670000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solder paste, and in particular to a solder paste without flux residue splash and a preparation method thereof. Background Art
[0002] At present, the 4G and 5G antenna filters of large base stations are devices with unique shapes and complex processing technology. The filter is processed and assembled from two silver-plated metal blocks. Its resonant cavity is very sensitive to shape and internal cleanliness. Therefore, it can only be fixed by mechanical assembly using a large number of screws, and the position of each screw needs to be carefully adjusted to ensure that the required signal parameters are obtained. This process cannot be realized through automation, requires a lot of manpower, is inefficient, and is costly. Some people have tried to use ordinary solder paste to assemble such antenna filters in an attempt to reduce the labor of screw assembly and fixation. However, when using ordinary solder paste, during the welding process, due to the presence of flux such as rosin in the flux, residual flux will overflow and splash, causing contamination of the inner wall of the filter resonant cavity and changes in the resonant parameters. Therefore, a lot of extra work is required to adjust them one by one. Although the manual operation in the welding fixation process can be reduced, the resonant parameters still need to be adjusted manually. Summary of the invention
[0003] In order to reduce the overflow and splashing of flux in the solder paste during the welding process, the present application provides a solder paste without flux residue and splashing and a preparation method thereof.
[0004] In the first aspect, the present application provides a solder paste with no flux residue and splash, which adopts the following technical scheme: a solder paste with no flux residue and splash, comprising a flux paste and a solder alloy powder, wherein the raw materials of the flux paste include the following components in parts by weight: 10 to 20 parts of epoxy resin, 3 to 10 parts of thermoplastic resin, 20 to 40 parts of activator, 5 to 15 parts of solvent, 15 to 25 parts of diluent, and 1 to 3 parts of thixotropic agent; the melting point of the thermoplastic resin is 80 to 140°C.
[0005] By adopting the above technical solution, adding thermoplastic resin to epoxy resin can alleviate the increase in viscosity, film formation, pad covering and other phenomena caused by the curing of epoxy resin. In addition, by adding solvent, thermoplastic resin can provide an additional compatible environment for materials such as solvents, and can provide a more relaxed space for solvent volatilization to escape, thereby further reducing the viscosity of solder paste and facilitating operation, thereby reducing the overflow and splashing of flux during the welding process.
[0006] In a specific embodiment, the weight ratio of the flux paste to the solder alloy powder is (8:92)-(30:70).
[0007] By adopting the above technical solution, the present application further defines the ratio of flux paste and solder alloy powder in the solder paste, thereby improving the performance of the prepared solder paste.
[0008] In a specific embodiment, the epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and alicyclic epoxy resin.
[0009] In a specific embodiment, the thermoplastic resin includes one or more of phenolic epoxy resin, phenoxy resin, ethylene-vinyl acetate copolymer, and polyester resin.
[0010] In a specific embodiment, the active agent includes one or more of malonic acid, succinic acid, glutaric acid, adipic acid, benzoic acid, and salicylic acid.
[0011] In a specific embodiment, the solvent includes one or more of ethylene glycol methyl ether, diethylene glycol butyl ether, diethylene glycol hexyl ether, methyl pentanediol, and triethylene glycol butyl ether.
[0012] In a specific embodiment, the diluent includes one or more of butanediol diglycidyl ether, hexanediol diglycidyl ether, tert-carbonate glycidyl ether, phenyl glycidyl ether, and trimethylolpropane triglycidyl ether.
[0013] In a specific embodiment, the thixotropic agent includes one or more of polyamide wax, polyethylene wax, and hydrogenated castor oil.
[0014] In a specific implementation manner, the raw materials of the soldering solder paste further include 0.5 to 2 parts by weight of a corrosion inhibitor, and the corrosion inhibitor includes one or more of benzotriazole, methylbenzotriazole, and phenylbenzotriazole.
[0015] By adopting the above technical solution, the addition of benzotriazole, methylbenzotriazole and phenylbenzotriazole can improve the corrosion resistance of the prepared solder paste.
[0016] In a second aspect, the present application provides a method for preparing a solder paste without flux residue splash, which adopts the following technical solution: A method for preparing solder paste without flux residue splashing comprises the following steps: The epoxy resin, the thermoplastic resin and the diluent are stirred and mixed evenly, heated until the resin is completely dissolved and then cooled to room temperature to obtain a mixture A; the thixotropic agent and the solvent are stirred and mixed evenly, heated until the thixotropic agent is completely dissolved and then cooled to room temperature to obtain a mixture B; Mixture A, mixture B, active agent and corrosion inhibitor are put into a stirrer and stirred at a speed of 10 to 80 rpm for 5 to 10 minutes. After being mixed evenly, they are ground with a three-roll mill to obtain solder paste; The solder alloy powder is gradually added to the solder paste, and then vacuum stirred at a rotation speed of 30 to 40 rpm for 20 to 40 minutes to obtain the solder paste.
[0017] By adopting the above technical scheme, the epoxy resin and the thermoplastic resin are first heated, mixed and dissolved to obtain a mixture A, and then the thixotropic agent is heated and dissolved in a solvent to obtain a mixture B; then the mixture A, the mixture B, the activator and the corrosion inhibitor are stirred and mixed, and ground to obtain a flux paste; finally, the flux paste and the solder alloy powder are vacuum stirred and mixed to obtain a solder paste with better performance.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, adding thermoplastic resin to epoxy resin can alleviate the phenomena of increased viscosity, film formation, and pad covering caused by curing of epoxy resin. Moreover, adding solvent can provide an additional compatible environment for materials such as solvent, and can provide a looser solvent volatilization escape space, thereby further reducing the viscosity of solder paste and facilitating operation. Therefore, the overflow and splashing of flux are reduced during the welding process. 2. The present application further defines the ratio of flux paste and solder alloy powder in the solder paste, thereby improving the performance of the prepared solder paste; 3. The method in the present application first heats, mixes and dissolves the epoxy resin and the thermoplastic resin to obtain a mixture A, and then heats and dissolves the thixotropic agent in a solvent to obtain a mixture B; then the mixture A, the mixture B, the activator and the corrosion inhibitor are stirred and mixed, and ground to obtain a flux paste; finally, the flux paste and the solder alloy powder are vacuum stirred and mixed to obtain a solder paste with better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a picture used in Example 1 of the present application to illustrate the condition of the welding surface after welding with solder paste.
[0020] Figure 2 This is a picture used in comparative example 1 of the present application to illustrate the condition of the welding surface after welding with solder paste.
[0021] Figure 3 This is a picture used in comparative example 2 of the present application to illustrate the condition of the welding surface after welding with solder paste. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] All raw materials in the embodiments can be obtained from the market. The solder alloy powder includes but is not limited to a mixture of one or more of Sn96.5Ag3.0Cu0.5, Sn99Ag0.3Cu0.7, Sn98.5Ag1Cu0.5, Sn42Bi58, Sn42Bi57Ag1, Sn42Bi57.6Ag0.4, Sn95Sb5, Sn10Sb10. Example
[0024] Example 1 Embodiment 1 provides a method for preparing a solder paste without flux residue splash, comprising the following steps: 10 kg of epoxy resin, 3 kg of thermoplastic resin and 15 kg of diluent were stirred and mixed at a speed of 100 rpm, heated in an oil bath at 150°C for 1 hour until the resin was completely dissolved, and then cooled to room temperature to obtain a mixture A; 1 kg of thixotropic agent and 5 kg of solvent were stirred and mixed at a speed of 100 rpm, heated in an oil bath at 100°C for 0.5 hour until the thixotropic agent was completely dissolved, and then cooled to room temperature to obtain a mixture B; wherein the epoxy resin is a mixture of alicyclic epoxy resin and bisphenol A epoxy resin, and the alicyclic epoxy resin and bisphenol A epoxy resin The weight ratio is 2:1; the thermoplastic resin is ethylene-vinyl acetate copolymer; the diluent is butanediol diglycidyl ether; the thixotropic agent is polyamide wax; the solvent is diethylene glycol butyl ether; the mixture A, the mixture B, and 20kg of the active agent are put into the stirrer and stirred at a speed of 50rpm for 10min. After mixing evenly, a three-roll mill is used to grind 3 times, and the grinding gap is GAP1=10μm, GAP2=5μm to obtain the solder paste; wherein the active agent is a mixture of malonic acid, adipic acid, and benzoic acid, and the weight ratio of malonic acid, adipic acid, and benzoic acid is 8:18:7; The solder alloy powder was gradually added to the flux paste, and then vacuum stirred for 30 minutes at a vacuum degree of -0.1 MPa and a rotation speed of 30 rpm to obtain the solder paste; wherein the solder alloy powder was Sn96.5Ag3.0Cu0.5; and the weight ratio of the flux paste to the solder alloy powder was 8:92.
[0025] Example 2 The difference between Example 2 and Example 1 is that mixed material A, mixed material B, 20 kg of active agent and 0.5 kg of corrosion inhibitor are put into a stirrer and stirred at a speed of 50 rpm for 10 min. After mixing evenly, a three-roll mill is used to grind 3 times with a grinding gap of GAP1=10 μm and GAP2=5 μm to obtain a solder paste; wherein the corrosion inhibitor is phenylbenzotriazole; and the remaining steps are consistent with Example 1.
[0026] Example 3 The difference between Example 3 and Example 2 is that 15 kg of epoxy resin, 7 kg of thermoplastic resin, and 20 kg of diluent are stirred and mixed at a speed of 100 rpm, stirred and heated in an oil bath at 150° C. for 1 hour until the resin is completely dissolved, and then cooled to room temperature to obtain a mixture A; 2 kg of thixotropic agent and 10 kg of solvent are stirred and mixed at a speed of 100 rpm, stirred and heated in an oil bath at 100° C. for 0.5 hour until the thixotropic agent is completely dissolved, and then cooled to room temperature to obtain a mixture B; Mixture A, mixture B, 30 kg of active agent and 1.5 kg of corrosion inhibitor were put into a stirrer and stirred at a speed of 50 rpm for 10 min. After mixing evenly, they were ground three times using a three-roll mill with a grinding gap of GAP1 = 10 μm and GAP2 = 5 μm to obtain solder paste; the remaining steps were consistent with Example 2.
[0027] Example 4 The difference between Example 4 and Example 2 is that 20 kg of epoxy resin, 10 kg of thermoplastic resin, and 25 kg of diluent are stirred and mixed at a speed of 100 rpm, stirred and heated in an oil bath at 150° C. for 1 hour until the resin is completely dissolved, and then cooled to room temperature to obtain a mixture A; 3 kg of thixotropic agent and 15 kg of solvent are stirred and mixed at a speed of 100 rpm, stirred and heated in an oil bath at 100° C. for 0.5 hour until the thixotropic agent is completely dissolved, and then cooled to room temperature to obtain a mixture B; Mixture A, mixture B, 40 kg of active agent and 2 kg of corrosion inhibitor were put into a stirrer and stirred at a speed of 50 rpm for 10 min. After mixing evenly, they were ground three times using a three-roll mill with a grinding gap of GAP1 = 10 μm and GAP2 = 5 μm to obtain solder paste; the remaining steps were consistent with Example 2.
[0028] Example 5 The difference between Example 5 and Example 3 is that the thermoplastic resin is phenoxy resin; the epoxy resin is a mixture of alicyclic epoxy resin and bisphenol F epoxy resin, and the weight ratio of alicyclic epoxy resin to bisphenol A epoxy resin is 8:7; the diluent is tert-butyl glycidyl ester; the solvent is diethylene glycol hexyl ether; the activator is a mixture of malonic acid, succinic acid and adipic acid, and the weight ratio of malonic acid, succinic acid and adipic acid is 4:1:8; and the remaining steps are consistent with Example 3.
[0029] Example 6 The difference between Example 6 and Example 3 is that the thermoplastic resin is polyester resin; the epoxy resin is alicyclic epoxy resin; the diluent is trihydroxypropane triglycidyl ether; the thixotropic agent is polyethylene wax; the solvent is diethylene glycol hexyl ether; the activator is a mixture of malonic acid, succinic acid and salicylic acid, and the weight ratio of malonic acid, succinic acid and salicylic acid is 8:12:5; the corrosion inhibitor is benzotriazole; and the remaining steps are consistent with Example 3.
[0030] Example 7 The difference between Example 7 and Example 3 is that the weight ratio of the flux paste to the solder alloy powder is 1:4; the remaining steps are consistent with Example 3.
[0031] Example 8 The difference between Example 8 and Example 3 is that the weight ratio of the flux paste to the solder alloy powder is 3:7; the remaining steps are consistent with Example 3.
[0032] Comparative Example Comparative Example 1 Comparative Example 1 is a rosin-based solder paste, model number is eup-148.
[0033] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that 13 kg of epoxy resin and 15 kg of diluent are stirred and mixed uniformly at a rotation speed of 100 rpm, stirred and heated at 150° C. for 1 hour in an oil bath until the resin is completely dissolved, and then cooled to room temperature to obtain a mixture A; the remaining steps are consistent with Example 1.
[0034] Performance test expansion rate: The solder paste in each embodiment is tested according to JIS Z3198-3:2003 "Expansion rate test", and the solder surface is observed to see if there is flux splashing.
[0035] Table 1 Performance test results of solder paste Combined with Example 1, Comparative Examples 1-2 and Figure 1-3 In the process of using the solder paste in Example 1, there is no flux splashing phenomenon and the expansion rate is relatively high. It can be seen that when preparing the solder paste, thermoplastic resin is added to the epoxy resin to alleviate the viscosity increase, film formation, and pad covering caused by the curing of the epoxy resin. Then, the solvent is added. The thermoplastic resin can provide an additional compatible environment for materials such as the solvent, and provide a more relaxed solvent volatilization escape space, thereby reducing the viscosity of the solder paste, facilitating the use and operation, improving the expansion rate of the solder paste, and reducing the flux splashing phenomenon during the welding process.
[0036] Combining Example 1 and Example 2, there is no obvious change in the expansion rate of the solder paste in Example 1 and Example 2. It can be seen that when preparing the solder paste, adding a corrosion inhibitor to the raw materials can improve the corrosion resistance of the prepared solder paste, but has little effect on the expansion rate of the solder paste.
[0037] In combination with Examples 2-4, the expansion rate of the solder paste in Example 3 is the highest. It can be seen that when preparing the solder paste, increasing the amount of raw materials used will cause the expansion rate of the prepared solder paste to first increase and then decrease.
[0038] In combination with Example 3, Example 5 and Example 6, there is no obvious change in the expansion rate of the solder paste in Example 3, Example 5 and Example 6. It can be seen that when preparing the solder paste, the epoxy resin is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and alicyclic epoxy resin, and the thermoplastic resin is selected from one or more of phenolic epoxy resin, phenoxy resin, ethylene-vinyl acetate copolymer, and polyester resin, and the obtained solder paste has a higher expansion rate.
[0039] Combining Example 3, Example 7 and Example 8, the expansion rate of the solder paste in Example 7 is the highest. It can be seen that when preparing the solder paste, when the weight ratio of the flux paste to the solder alloy powder is (8:92)-(30:70), increasing the weight ratio of the two, the expansion rate of the obtained solder paste shows a trend of first increasing and then decreasing.
[0040] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A solder paste without flux residue splash, characterized by: The invention comprises solder paste and solder alloy powder. The raw materials of the solder paste comprise the following components in parts by weight: 10 to 20 parts of epoxy resin, 3 to 10 parts of thermoplastic resin, 20 to 40 parts of activator, 5 to 15 parts of solvent, 15 to 25 parts of diluent and 1 to 3 parts of thixotropic agent. The melting point of the thermoplastic resin is 80 to 140°C.
2. The solder paste without flux residue splash according to claim 1, characterized in that: The weight ratio of the flux paste to the solder alloy powder is (8:92)-(30:70).
3. The solder paste without flux residue splash according to claim 1, characterized in that: The epoxy resin includes one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and alicyclic epoxy resin.
4. The solder paste without flux residue splash according to claim 1, characterized in that: The thermoplastic resin includes one or more of phenolic epoxy resin, phenoxy resin, ethylene-vinyl acetate copolymer, and polyester resin.
5. The solder paste without flux residue splash according to claim 1, characterized in that: The active agent includes one or more of malonic acid, succinic acid, glutaric acid, adipic acid, benzoic acid, and salicylic acid.
6. The solder paste without flux residue splash according to claim 1, characterized in that: The solvent includes one or more of ethylene glycol methyl ether, diethylene glycol butyl ether, diethylene glycol hexyl ether, methyl pentanediol, and triethylene glycol butyl ether.
7. The solder paste without flux residue splash according to claim 1, characterized in that: The diluent includes one or more of butanediol diglycidyl ether, hexanediol diglycidyl ether, tert-carbonate glycidyl ether, phenyl glycidyl ether, and trimethylolpropane triglycidyl ether.
8. The solder paste without flux residue splash according to claim 1, characterized in that: The thixotropic agent includes one or more of polyamide wax, polyethylene wax and hydrogenated castor oil.
9. The solder paste without flux residue splash according to claim 1, characterized in that: The raw materials of the soldering solder paste further include 0.5 to 2 parts by weight of a corrosion inhibitor, wherein the corrosion inhibitor includes one or more of benzotriazole, methylbenzotriazole, and phenylbenzotriazole.
10. A method for preparing a solder paste without flux residue splash as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The epoxy resin, the thermoplastic resin and the diluent are stirred and mixed evenly, heated until the resin is completely dissolved and then cooled to room temperature to obtain a mixture A; the thixotropic agent and the solvent are stirred and mixed evenly, heated until the thixotropic agent is completely dissolved and then cooled to room temperature to obtain a mixture B; Mixture A, mixture B, active agent and corrosion inhibitor are put into a stirrer and stirred at a speed of 10 to 80 rpm for 5 to 10 minutes. After being mixed evenly, they are ground with a three-roll mill to obtain solder paste; The solder alloy powder is gradually added to the solder paste, and then vacuum stirred at a rotation speed of 30 to 40 rpm for 20 to 40 minutes to obtain the solder paste.
Citation Information
Patent Citations
Halogenide-free leadless soldering tin paste
CN101327553A
Lead-free and cleaning-free solder paste capable of realizing few-cavity welding layers and preparation method of lead-free cleaning-free solder paste
CN102528315A
Epoxy resin soldering flux as well as preparation method and application thereof
CN106281171A
No-clean flux high in welding passing rate
CN106392380A
High-quality soldering paste
CN106392381A